Factors affecting corporate social responsibilities disclosure of listed companies in Vietnam - Quynh Lien Le; Lan Huong Nguyen; Viet Hoa Dinh; Thi Thu Huyen Luong; Thi Khanh Linh Pham; Thi Hai Ly Nguyen (Cogent Business & Management, 2023)
This paper aims to research factors that affect corporate social responsibility (CSR) disclosure in the context of listed companies in Vietnam. Our research uses data from listed companies in the Hanoi and Ho Chi Minh City Stock Exchanges from 2015 to 2020. We conduct the quantitative research by analyzing regression models therefore the relation between factors and CSR disclosure is found. We measure CSR disclosure in two ways: by total score and percentage. The result found that in both ways of measuring, the percentage of women on board and company age have a positive impact on CSR disclosure. In contrast to this, board size and board age have a negative effect on CSR disclosure. The other independent variables have no impact on CSR disclosure. Therefore, we have given some practical implications for companies that want to improve their CSR disclosure.
Keywords: 650; Corporate social responsibility; Corporate social responsibility disclosure; Vietnam listed companies